2022
DOI: 10.1002/acn3.51565
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy to detect early immune‐mediated small nerve fibre loss in AL amyloidosis

Abstract: Objective: Light chain (AL) amyloidosis is a life-threatening disorder characterised by extracellular deposition of amyloid leading to dysfunction of multiple organs. Peripheral nerve involvement, particularly small fibre neuropathy, may be associated with poorer survival. Corneal confocal microscopy (CCM) is a rapid and non-invasive imaging technique to quantify corneal small nerve fibres and immune cells in vivo. We aimed to evaluate CCM as a tool for early diagnosis of peripheral nerve involvement in AL amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…In contrast to inflammatory neuropathies [21, 22], and neuropathies due to systemic diseases like light chain amyloidosis [48] and other monogenetic disorders like hereditary transthyretin amyloidosis [49], corneal immune cell infiltration was not found in our cohort of patients with SMA. This underlines neurodegeneration related to SMN1 mutations as the main mechanism in SMA pathogenesis, which does not trigger autoimmunity, accompanied with secondary inflammation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast to inflammatory neuropathies [21, 22], and neuropathies due to systemic diseases like light chain amyloidosis [48] and other monogenetic disorders like hereditary transthyretin amyloidosis [49], corneal immune cell infiltration was not found in our cohort of patients with SMA. This underlines neurodegeneration related to SMN1 mutations as the main mechanism in SMA pathogenesis, which does not trigger autoimmunity, accompanied with secondary inflammation.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to inflammatory neuropathies [21,22], and neuropathies due to systemic diseases like light chain amyloidosis [48] and…”
Section: Discussionmentioning
confidence: 99%
“…A QST study is based on the determination of temperature and temperature-induced pain thresholds, which allows assessment of the function of smaller myelinated and unmyelinated sensory fibers -Aδ and C 19,29 . Thimm et al 30 revealed significant subclinical small nerve fiber damage in the cornea in patients with SMA type 3, which correlated with motor function. In our QST study, the most significant differences were related to cold pain threshold.…”
Section: Discussionmentioning
confidence: 98%
“…IVCM is a noninvasive imaging technique that allows the direct visualization of the corneal structure, including the corneal sub-basal nerve plexus in vivo. For this reason, IVCM has been used to identify small nerve fiber damage in several peripheral neuropathies, such as diabetic neuropathy, and in immune-mediated SFN such as amyloidosis [8,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%